PERANAN SUPERVISOR DALAM MEMOTIVASI DI BANQUET SECTION HOTEL PANGERAN PEKANBARU - Kamal, Musatafa; Rifiyan, Andi M (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This study aimed About the Role of the Supervisor in Motivating In Section Banquet Hotel Pangeran Pekanbaru. This study aims to: (1) To determine the role in carrying out its duties and responsibilities in Operations. (2) To determine the role of supervisors in motivating employees at the banquet section Pangeran Hotel Pekanbaru.This research uses descriptive quantitative method for describing the problem in the company. The sample used in this study were 8 people.Based on the research that has been done, the result for the Supervisor Role In Meotivation In Section Banquet Hotel Pangeran Pekanbaru is good enough. This is evidenced by the acquisition of a total overall score, which is 567 points.Keywords: Credibility, Confidence, Pressure From Group, Personal Problems,Feelings Isolated, Less Skilled, Influence Prospects HotelFamily problems, been suspended, Saturation